2013
DOI: 10.4187/respcare.02166
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Aberration Associated with Bronchopulmonary Dysplasia in Preterm Infants: A Preliminary Study

Abstract: BACKGROUND: Because environmental insults and genetic factors account for the variance in the risk of bronchopulmonary dysplasia (BPD) in very low birth weight (VLBW, birth weight < 1,500 g) preterm infants, the search for BPD biomarkers has begun to focus on the regulators of non-coding RNA such as microRNAs (miRNAs). Therefore, this study aimed to identify potential miRNAs involved in the pathogenesis of BPD in VLBW preterm infants. METHODS: A case-control study (15 subjects with BPD and 15 sex-matched contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…There are only limited existing data to evaluate the impact of including such heterogeneous subgroups of participants in the analysis on the findings. For example, among the 23 miRNAs with age-limited expression and 101 differentially expressed miRNAs, one (miR-652) was up-regulated in schizophrenia (Lai et al ., 2011), and three others were either down-regulated (miR-152) or up-regulated (miR-133b and miR-7) in bronchopulmonary dysplasia (Wu et al ., 2013), all in peripheral blood. Meanwhile, among the 101 differentially expressed miRNAs, 12 (Tables S4 and S5) were found to be down-regulated in the postmortem brain tissue of patients with schizophrenia (Gardiner et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are only limited existing data to evaluate the impact of including such heterogeneous subgroups of participants in the analysis on the findings. For example, among the 23 miRNAs with age-limited expression and 101 differentially expressed miRNAs, one (miR-652) was up-regulated in schizophrenia (Lai et al ., 2011), and three others were either down-regulated (miR-152) or up-regulated (miR-133b and miR-7) in bronchopulmonary dysplasia (Wu et al ., 2013), all in peripheral blood. Meanwhile, among the 101 differentially expressed miRNAs, 12 (Tables S4 and S5) were found to be down-regulated in the postmortem brain tissue of patients with schizophrenia (Gardiner et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The screening set consisted of preterm infants ( n = 30, mean gestational age = 29.1 weeks) and adults ( n = 60, mean age = 37 years), and the validation set consisted of independent samples of preterm infants ( n = 22, mean gestational age = 28.9 weeks), children ( n = 66, mean age = 9.1 years), and adults ( n = 68, mean age = 36.9 years). For the preterm infants, we enrolled very-low-birth-weight preterm infants who were admitted to the neonatal intensive care unit at the National Taiwan University Hospital and Mackey Memorial Hospital in Taipei, Taiwan, from September 2008 to December 2009, as described in more detail in a previous study (Wu et al ., 2013). Briefly, the inclusion criteria included gestational age ≤ 33 weeks, birth weight < 1500 g, absence of congenital and chromosomal abnormalities, and infants who were born in or admitted to the neonatal intensive care unit within 7 days of birth.…”
Section: Methodsmentioning
confidence: 99%
“…In both mice and human lung tissues, DNA methylation, another form of epigenetic regulation, has been shown to alter expression of genes associated with lung development and alveolar septation including a number of genes in angiogenic pathways [75]. Several studies have also shown that epigenetic regulation by microRNA expression is aberrant in BPD [76, 77]. Transgenic miR-150 knockout mice demonstrate increased angiogenesis when exposed to neonatal hyperoxia that may be due to upregulation of glycoprotein non-metastatic melanoma protein B (GPNMB) [78].…”
Section: Introductionmentioning
confidence: 99%
“…One study reported expression profiles of miRNA in peripheral blood of late-preterm infants with and without BPD (Wu et al, 2013). A 4-miRNA signature was identified as characterizing preterm infants with BPD.…”
Section: The Epigenetic Contribution To the Developmental Origins Of mentioning
confidence: 99%
“…A 4-miRNA signature was identified as characterizing preterm infants with BPD. The miRNAs that differed in magnitude between preterm infants with BPD and those without were miR-152, miR-30a-3p, miR-133b, and miR-7 (Wu et al, 2013). The presence of a miRNA signature in peripheral blood that might serve as a biomarker is an exciting prospect.…”
Section: The Epigenetic Contribution To the Developmental Origins Of mentioning
confidence: 99%